DyTE: An Effective Routing Protocol for VANET in Urban Scenarios - Kazi, A. K.; Khan, S. M. (Engineering, Technology & Applied Science Research, 2021)
A Vehicular Ad-hoc Network (VANET) is a subclass of wireless ad-hoc networks, widely used in on-road vehicles and roadside equipment, having applications in various areas including passenger safety, smart traffic solutions, and connectivity on vehicles The VANET is the backbone of the Intelligent Transport System (ITS) that establishes connectivity between vehicles through a wireless medium. When it comes to the communication between high-speed vehicles there is the challenge of dynamic mobility. In order to provide a higher Packet Delivery Ratio (PDR) and increase the throughput, a new routing protocol called Dynamic Trilateral Enrolment (DyTE) is introduced which chooses a dynamic trilateral zone to find the destination vehicle by allowing only relevant nodes to participate in the communication process using the location coordinates of source and destination nodes. The proposed routing protocol is compared with Ad-hoc On-demand Distance Vector (AODV), Ad-hoc On-demand Multipath Distance Vector (AOMDV), and Dynamic Source Routing (DSR), and the results show remarkable improvement in reducing the Network Routing Load (NRL) and increasing the PDR and throughput of the network. DyTE has performed more efficiently in terms of PDR (23% approximately), throughput (26% approximately) and drastically minimized the NRL by a factor of almost 3.